Case Report: A Novel Mutation in the Mitochondrial MT-ND5 Gene Is Associated With Leber Hereditary Optic Neuropathy (LHON) - Engvall, Martin; Kawasaki, Aki; Carelli, Valerio; Wibom, Rolf; Bruhn, Helene; Lesko, Nicole; Schober, Florian A.; Wredenberg, Anna; Wedell, Anna; Träisk, Frank (Frontiers in Neurology, 2021)
Leber hereditary optic neuropathy (LHON) is a mitochondrial disease causing severe bilateral visual loss, typically in young adults. The disorder is commonly caused by one of three primary point mutations in mitochondrial DNA, but a number of other rare mutations causing or associated with the clinical syndrome of LHON have been reported. The mutations in LHON are almost exclusively located in genes encoding subunits of complex I in the mitochondrial respiratory chain. Here we report two patients, a mother and her son, with the typical LHON phenotype. Genetic investigations for the three common mutations were negative, instead we found a new and previously unreported mutation in mitochondrial DNA. This homoplasmic mutation, m.13345G>A, is located in the MT-ND5 gene, encoding a core subunit in complex I in the mitochondrial respiratory chain. Investigation of the patients mitochondrial respiratory chain in muscle found a mild defect in the combined activity of complex I+III. In the literature six other mutations in the MT-ND5 gene have been associated with LHON and by this report a new putative mutation in the MT-ND5 can be added.